Depicting socioeconomic disadvantage and social gradient in quality of life in Limassol, Cyprus. (20th October 2021) - Middleton, N; Theodorou, E; Panayiotou, A; Kleopa, D; Ellina, P; Kouta, C
Abstract: Background: The lack of validated and accepted area-level indices of socioeconomic disadvantage at national or regional level in Cyprus poses a barrier to "spatial thinking" among Public Health policy-makers and researchers. Methods: A composite index of socioeconomic disadvantage was constructed by exploring the factor structure of 28 commonly used census indicators at city quarter (N = 38, median population 3894, IQR 2570-6169) and postcode level (N = 124, median 1320, IQR 798-2014). Predictive validity was explored in mixed random-effect regression models in term of associations with SF-36 health-related quality of life among a stratified random sample aged 45-64 (N = 450, 45 neighbourhoods). Results: There was wide variability across communities in all indicators, for instance, 0.4%-25.9% unemployment, 41.1%-90.7% at most secondary level education, 3.6%-95.9% residences built prior to 1980. Two factors were identified: "socioeconomic disadvantage" (SED), with the same set of 11-12 indicators at the two levels of geographical aggregation, and "built environment", reflecting proximity to the city centre, with nevertheless no meaningful associations with the outcome of interest. The SED index captured a stepwise decrease in physical (-1.39 95%CI -2.06, -0.72) and mental health (-1.26 95% -1.98, -0.54) scores across quartiles of postcodes with increasing disadvantage, of similar clinically significant effect size by gender. Associations attenuated slightly but remained significant after adjusting for person-based indicators of social position, with some weak evidence of cross-level interactions for physical, but not mental, health. Conclusions: The composite index, tapping on educational, economic, material, occupational and social disadvantage, allowed the exploration of socioeconomic disadvantage patterning at a small-area level in the city of Limassol and documented the social gradient in health-related quality of life among a late working-life sample of residents. Key messages: First-time depiction of the geographical patterning of socioeconomic disadvantage across the small geographical level of postcodes in the city of Limassol, Cyprus. Social gradient in physical and mental health in men and women across the continuum of socioeconomic disadvantage over and above person-based indicators of social position.